2017
DOI: 10.1089/dia.2016.0372
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Glycemic Fluctuations in Patients with Type 2 Diabetes: Approaches and Importance

Abstract: Glycemic fluctuations, characterized by short-term oscillations in plasma glucose, are important when managing type 2 diabetes (T2D) and may be considered a target of glucose-lowering therapies. Continuous glucose monitoring (CGM) has been used to evaluate the effects of different treatments on glycemic fluctuations. This review examines approaches to and the importance of minimizing glycemic fluctuations among patients with T2D. Measures of HbA1c, fructosamine, and glycated albumin reflect a long-term average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 61 publications
2
42
0
Order By: Relevance
“…[31][32][33][34][35] As measurements of HbA 1c do not reflect glycemic variability and target HbA 1c values may be achieved while still experiencing marked daily glycemic fluctuations, people with T1D may regard reducing glucose variability and improving TIR to be as important as achieving their target HbA 1c value. 36,37 The study data also confirmed that missing bolus injections can be common for people with T1D, where on average at least 25% of meals had a missed dose, assuming three meals per day. This amounts to five meals with a missed dose per week on average.…”
Section: Discussionsupporting
confidence: 61%
“…[31][32][33][34][35] As measurements of HbA 1c do not reflect glycemic variability and target HbA 1c values may be achieved while still experiencing marked daily glycemic fluctuations, people with T1D may regard reducing glucose variability and improving TIR to be as important as achieving their target HbA 1c value. 36,37 The study data also confirmed that missing bolus injections can be common for people with T1D, where on average at least 25% of meals had a missed dose, assuming three meals per day. This amounts to five meals with a missed dose per week on average.…”
Section: Discussionsupporting
confidence: 61%
“…Intermittent high blood glucose spikes, as opposed to constant exposure to high blood glucose, has been shown to promote damaging effects [ 10 , 12 , 38 ]. Daily glucose fluctuations are incompletely expressed by HbA1c alone, particularly in patients considered to have good metabolic control or with prediabetes [ 9 , 13 , 36 , 39 , 40 ]. To date, few studies have examined the effects of RT-CGM on GV.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, evaluation of various drug types on markers of GV or MeS was not performed. Previous studies have demonstrated that an increase in oral hypoglycaemic medications may sometimes result in a drop in MAGE [ 40 ]. To better understand the clinical implications of RT-CGM on GV, future trials should closely monitor and consider medication types, doses and changes in dose over the time course of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes (T2D) affects 30.3 million people (~ 9.4% of the population) in the USA as of 2017 [ 1 ]. The economic and social costs of T2D are considerable because of its associated serious short- and long-term complications, particularly in patients who do not achieve and/or maintain glycemic control [ 2 , 3 ], as well as its significant contribution to overall mortality (approximately 12% of all deaths) [ 4 ]. Hyperglycemia, which may result from insufficient treatment intensification, significantly increases the risks of microvascular complications, such as retinopathy and nephropathy, as well as macrovascular complications including myocardial infarction, heart failure, stroke, and their composite [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%